HTML5 Developer's Cookbook - Hudson, Chuck, 1969 and Leadbetter, Tom, 1983- (New Delhi Pearson, 2012)
Provides information on using HTML5 to create standards-based browser applications that incorporate drag-and-drop, audio, video, and third-party plug-ins.
Keywords: Web site development